Understanding loss of consciousness under general anaesthesia using multimodal neuroimaging - Holmgren, J (2021)
Despite major advancements in consciousness science over the past few decades, how anaesthesia causes loss of consciousness remains incompletely understood and the translation from basic science to clinical practice has been limited. Recent concurrent electroencephalography (EEG) and functional magnetic resonance imaging (FMRI) evidence indicates that a state of complete perception loss is achieved under general anaesthesia when slow wave activity in the brain reaches saturation. Slow wave activity saturation (SWAS) is therefore a potentially clinically relevant end point for titration of anaesthesia.